This volume is dedicated to Prof. P.G. Goussard, editor of this Journal since September 1989 – September 2005. - Team, Editorial (South African Journal of Enology and Viticulture, 2017)
The Journal of the South African Society for Enology and Viticulture was established in 1980 and has commemorated its 25th birthday during this year. Prof. Goussard, Professor at the Department of Viticulture and Oenology at the University of Stellenbosch, became editor in 1989 and has been instrumental in the expansion of this flagship of the Society to one of the most important journals in viti- and viniculture in the world. As an world-renowned expert in many areas of viticulture, he was also the recipient of the prestigious SASEV prize during 1992 and various other awards. During his career as editor, he made many changes to the journal, including the appearance of the journal during 2001. He was also the editor of a special edition of the journal in 2000, commemorating the 5th birthday of The Institute for Wine Biotechnology at the University of Stellenbosch. As editor from 1989 – 2005, more than 33 journals were published.